Psychological barriers to the occupational success of mature women - Kahn, Sharon E. (Canadian Journal of Counselling and Psychotherapy, 2012)
This paper presents a description of the barriers to successful achievement outside the home faced by many women in mid-life. Cultural myths about women and the nature of work may prevent mature women from fully participating in self-development other than as wives and mothers. Counselling theory has been effected by these myths. Counsellors are encouraged to facilitate self-exploration and conflict resolution with mature women who may be experiencing the mid-life crisis of changing roles from full-time mother to paid worker.